Respuesta :

-5 will be your answer. Hope this helps!

Answer:

z = -5

Step-by-step explanation:

To find the value of z in the equation 11 + z = 6

we will simply subtract 11 from both-side of the equation. That is;

11 + z = 6

Subtract 11 from both-side of the equation

11 - 11 + z  = 6 - 11

(On the left-hand side of the equation 11 will be subtracted from 11 which gives zero, thereby leaving us with just z while on the right-hand side of the equation 11 will be subtracted from 6 which will give negative 5)

z = -5